Numerical modelling of steel beam-columns in case of fire - Comparisons with Eurocode 3 - Vila Real, P.M.M. (2010)
This paper presents a numerical study of the behaviour of steel I-beams subjected to fire and a combination of axial force and bending moments. A geometrical and material non-linear finite element program, specially established in Liege for the analysis of structures submitted to fire, has been used to determine the resistance of a beam-column at elevated temperature, using the material properties of Eurocode 3, part 1–2. The numerical results have been compared with those obtained with the Eurocode 3, part 1–2 (1995) and the new version of the same Eurocode (2002). The results have confirmed that the new proposal for Eurocode 3 (2002) is more conservative than the ENV-EC3 (1995) approach.